Memory, meaning & method - Stevick, Earl W. (Heinle & Heinle Publishers, 1996)
Heinle & Heinle Publishers celebrates the 20th anniversary of Memory, Meaning & Method with this thoroughly revised edition. The well-known original text moved from careful attention to the research literature, to an original and personal statement about the role of the language teacher. Now, drawing on a wide range of material (more than three-quarters of which is new) Stevick restates, and where necessary modifies, his classic account of what goes on in the learning and teaching of languages.